A TaqMan Assay for the Detection and Monitoring of Potentially Invasive Lasiocampids, With Particular Attention to the Siberian Silk Moth, Dendrolimus sibiricus (Lepidoptera: Lasiocampidae). Issue 1 (1st February 2023) - Stewart, Don; Djoumad, Abdelmadjid; Holden, Dave; Kimoto, Troy; Capron, Arnaud; Dubatolov, Vladimir V; Akhanaev, Yuriy B; Yakimova, Maria E; Martemyanov, Vyacheslav V; Cusson, Michel
Abstract: The Siberian silk moth, Dendrolimus sibiricus Tschetverikov, is a very serious pest of conifers in Russia and is an emerging threat in North America where an accidental introduction could have devastating impacts on native forest resources. Other Dendrolimus Germar species and related Eurasian lasiocampids in the genus Malacosoma (Hubner) could also present a risk to North America's forests. Foreign vessels entering Canadian and U.S. ports are regularly inspected for Lymantria dispar (Linnaeus) and for the presence of other potentially invasive insects, including suspicious lasiocampid eggs. However, eggs are difficult to identify based on morphological features alone. Here, we report on the development of two TaqMan (Roche Molecular Systems, Inc., Rotkreuz, Switzerland) assays designed to assist regulatory agencies in their identification of these insects. Developed using the barcode region of the cytochrome c oxidase I (COI) gene and run in triplex format, the first assay can detect Dendrolimus and Malacosoma DNA, and can distinguish North American from Eurasian Malacosoma species. The second assay is based on markers identified within the internal transcribed spacer 2 (ITS2) region and was designed to specifically identify D. sibiricus, while discriminating closely related Dendrolimus taxa. In addition to providing direct species identification in the context of its use in North America, the D. sibiricus assay should prove useful for monitoring the spread of this pest in Eurasia, where its range overlaps with those of the morphologically identical D. superans (Butler) and similar D. pini (Linnaeus). The assays described here can be performed either in the lab on a benchtop instrument, or on-site using a portable machine.